EFFECT OF PRECONDITIONS AND UNSAFE ACTS ON EVACUATION DURATION IN FIRE DISASTER CONDITIONS (STUDY AT THE INPATIENT BUILDING OF GENERAL HOSPITAL R. KOESMA TUBAN - Erwin Era Prasetya; Denny Ardyanto W; Hari Basuki Notobroto; Tjipto Suwandi (Universitas Airlangga, 2021)
ABSTRACTHospital fires have the potential to cause fatalities and huge material losses, there were 22 hospital fires covered by newspapers in India in 2011-2012 with 102 dead. Buildings are considered safe if all occupants building threatened by fire must be able to exit and assembly point before available safe egress time. This study aimed to analyze the effect of preconditions and unsafe acts (violations of evacuation procedures) on evacuation duration in fire disaster conditions in the inpatient building of general hospital R. Koesma Tuban. This study was an observational study, a quantitative method and cross sectional design, which were carried out in April-July 2019. Analysis of Covariance test results stated preconditions (age, sex, exercise habits, location of inpatient ward, distance traveled) affect the duration of evacuation (p <0.05) while preconditions (interaction between workers and readiness of workers) don’t affect the duration evacuation (p> 0.05). Violation of evacuation procedures has the potential to influence the duration of evacuation (p = 0.054). The conclusions this study are age, gender, exercise habits, location of the inpatient ward, and distance traveled affect the duration of the evacuation. Keywords: Duration of evacuation, preconditions, violations of evacuation procedures, hospital